Hubungan Tingkat Pengetahuan Penggunaan Analgetik Terhadap Tingkatan Status Mahasiswa Fakultas Kedokteran - Martin Yudi; Devi Nur Fadjri (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2022)
Complaints and discomfort due to pain often make a person perform self-medication, where a person chooses to carry out independent handling of the perceived complaint by treating and curing the complaint. Sufficient knowledge will influence the individual to be careful in choosing the appropriate type of drug starting from the drug content to the impact on the success of treatment therapy. The use of analgesics is still often done because of the public perception of the practicality of using drugs in overcoming minor ailments such as pain. The research was conducted to determine the relationship between the level of analgesic use and the status level of students of the Faculty of Medicine, University of Muhammadiyah Malang. The cross sectional research approach used a total random sampling technique of 114 respondents. Data analysis using Chi-Square test. The results showed that as many as 79 respondents (69.29%) had a good level of knowledge, 18 respondents (15.80%) had a sufficient level of knowledge and 17 respondents (14.91%) had a low level of knowledge.This shows that the level of knowledge about the use of analgesics as treatment is at a good level and the relationship between the level of use of analgesics as treatment and the level of student status at the Faculty of Medicine, University of Muhammadiyah Malang (p <0.05). The level of knowledge about the use of analgesics as pain management in pre-clinical and professional students at the Faculty of Medicine UMM was in the good category.